Fixed-time control of a class of fractional-order chaotic systems via backstepping method. (February 2023) - Luo, Runzi; Liu, Shuai; Song, Zijun; Zhang, Fang
Abstract: This paper investigates the fixed-time control of a class of fractional-order systems via the backstepping method. A new fractional-order fixed-time stability theorem, which is a generalization of the integer order stability theorem, is presented. By using the proposed stability theorem, the fixed-time control problem of a class of fractional-order chaotic systems is investigated. Some fixed-time convergence criteria which have some pretty properties such as no singularity and no chattering are presented via backstepping method. Simulation results are given to show the effectiveness of the presented results.